CHARACTERISTICS OF CARRAGENAN (Eucheuma cottonii) EXTRACTED WITH KOH - Rusnawati Rusnawati; Andarini Diharmi; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT  The purpose of this study was to determine the chemical composition of dried Eucheuma cottonii and physico-chemical characteristicsof carrageenan were extracted with Potassium hydroxida (KOH) solutions 4, 8, and 12% was obtained from Northern Rupat and Riau Islands. The results of analysis showed that the chemical composition of dried Eucheuma cottonii of both costal sea regions was not different, with the chemical composition value of moisture (7.99-11.45%), ash (22.84-36.52%),acid-insoluble ash (1.66-2.25%), and sulfate content (22.46-29.64%), those were not difference in all carrageenan except ash content, whereas the physical characteristics of both carrageenan are significantly different. The results of this study indicate that the carrageenan was extracted with KOH (4, 8, and 12%) only affects the physico-chemical characteristics of gel strenght, viscosity and carrageenan ash content. Keywords:carrageenan, Eucheuma cottonii, extraction, gel strength, KOH